Utilization Of Indonesian Language-Based Ai Chatbot For Digital Public Services - Feberlina Hulu (CV. SINAR HOWUHOWU, 2026)
The rapid development of artificial intelligence (AI) has significantly transformed public service sectors, particularly through the implementation of chatbot technology. This study aims to analyze the utilization of Indonesian-language-based chatbots in improving the efficiency, accessibility, and interactivity of digital public services in Indonesia. A qualitative approach was employed by combining literature review and case analysis of chatbot implementation in government institutions. The results indicate that chatbots equipped with natural language processing (NLP) in the Indonesian language can accelerate service responses, reduce staff workload, and enhance citizen satisfaction. Nevertheless, several challenges remain, including limited understanding of local language context, data security concerns, and the readiness of government digital infrastructure. This study recommends strengthening collaboration among government, academia, and AI developers to build an inclusive and efficient digital public service ecosystem in the future.